Оцінка впливу основних конструкторсько-технологічних чинників на чутливість приладу на основі явища поверхневого плазмонного резонансу - Дорожинський, Гліб Вячеславович (НТУ "ХПІ", 2015)
Розглядається залежність чутливості приладу на основі поверхневого плазмонного резонансу від шорсткості поверхні металевого шару його чутливого елементу та довжини хвилі збудження поверхневих плазмонів. Встановлено, що зменшення шорсткості поверхні металевого шару та збільшення довжини хвилі викликає підвищення чутливості при вимірюванні зміни інтенсивності відбитого світла та зменшення чутливості при вимірюванні зсуву мінімуму характеристики відбиття. Результати досліджень можуть бути використані для вдосконалення існуючих та створення нових приладів на основі поверхневого плазмонного резонансу.

We consider the dependence of the sensitivity of the instrument based on surface plasmon resonance surface roughness of the metal layer and its sensing element excitation wavelength surface plasmons. The sensitivity of SPR-device "Plasmon-6" in the mode of measuring the intensity of the reflected light with increasing surface roughness sensing element from 0 to 20 nm is 2 times decreased from 5.13 V/deg to 2.82 V/deg. This is due to a decrease in left slope steepness reflection characteristics R (и) as a result of its expansion. By increasing the laser wavelength of 650 ... 1200 nm sensitivity of the device increases 5 times with 5.13 V/deg to 26 V/deg result, due to the increase in the steepness of the slope left reflection characteristics R (и). At wavelengths smaller than 589 nm to 650 nm and a minimum reflection characteristics R (и) is weakly expressed extreme, and the shape of the curve is substantially asymmetric and sensitivity of the device is less than 5.13 V/deg. At wavelengths 1200 nm reflectance characteristics at the minimum reflectance R (и) increases to 0.2, which reduces the dynamic range of angular measurement. The practical significance is that the results of numerical analysis can be used to improve existing and create new devices based on surface plasmon resonance.
Assessment of influence basic design and technological factors on the sensitivity of the device based on the phenomenon of surface plasmon resonance
Keywords: оптичні методи вимірювання; рефрактометричний метод; шорсткість поверхні; довжина хвилі випромінювання; surface plasmon resonance; sensitivity; wavelength of the radiation; surface roughness